Synthesis and Antifungal Activity of Some Bis(2-arylimino-3-yl-thiazolidinones) and Bis-(1-aryl-3-yl-2-thiohydantoins) - Shah, V.; Pant, C.K.; Joshi (Jr.), P.C. (Asian Journal of Chemistry, 2010)
Some bis-(2-arylimino-3-yl-4-thiazolidin-4-ones) and bis-(1-aryl-3-yl- 2-thiohydantoins) were synthesised from bis-(4-aryl-3-thiocarbamides) and screened for their antifungal activity against Aspergillus flavus, Helminthosporium tetramera and Pennicillium decombens.